2021
DOI: 10.1177/17562864211012835
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to COVID-19 mRNA vaccine in patients with multiple sclerosis treated with high-efficacy disease-modifying therapies

Abstract: Background and Aims: The National Multiple Sclerosis Society and other expert organizations recommended that all patients with multiple sclerosis (MS) should be vaccinated against COVID-19. However, the effect of disease-modifying therapies (DMTs) on the efficacy to mount an appropriate immune response is unknown. We aimed to characterize humoral immunity in mRNA-COVID-19 MS vaccinees treated with high-efficacy DMTs. Methods: We measured SARS-CoV-2 IgG response using anti-spike protein-based serology (EUROIMMU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
336
11
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(399 citation statements)
references
References 23 publications
45
336
11
7
Order By: Relevance
“…Until now, only one study investigated humoral immune response to COVID-19 vaccine in PwMS treated with high efficacy DMTs (Achiron et al, 2021). Patients were vaccinated exclusively with Pfizer-BioNTech vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only one study investigated humoral immune response to COVID-19 vaccine in PwMS treated with high efficacy DMTs (Achiron et al, 2021). Patients were vaccinated exclusively with Pfizer-BioNTech vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about cell-mediated responses in patients receiving B-cell depleting therapies after SARS-CoV-2 natural infection or vaccination (Asplund Högelin et al, 2021), while several case reports have demonstrated the absence of detectable anti-SARS-CoV-2 antibodies (Ab) (Iannetta et al, 2020;Khayat-Khoei et al, 2021;Smets et al, 2021;Thornton and Harel, 2020). Recently, Achiron et al showed poor seroconversion rates after SARS-CoV-2 vaccination in MS patients receiving B-cell depleting treatments (Achiron et al, 2021). The role of T-cell responses in terms of protection against SARS-CoV-2 infection and re-infection needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Protection through immunization is achieved by an orchestrated immune response between different cellular subsets of innate (APCs) and adaptive immunity, such as B and T cells. Anti-B cell therapies like anti-CD20 antibodies (rituximab, obinutuzumab and ocrelizumab) and BTK inhibitors are associated with poor humoral SARS-CoV-2 vaccination responses, in patients with AIIRD[17][18][19][20] , multiple sclerosis26…”
mentioning
confidence: 99%